2004
DOI: 10.1002/ejsp.222
|View full text |Cite
|
Sign up to set email alerts
|

Multiculturalism and group status: The role of ethnic identification, group essentialism and protestant ethic

Abstract: The present research, which was conducted among ethnic minority (N ¼ 109) and majority (N ¼ 649) adolescents in the Netherlands, examined the endorsement of multiculturalism in relation to ethnic ingroup identification, perceived group essentialism and protestant ethic ideology. The results revealed that ethnic minorities were more in favour of multiculturalism than Dutch participants. Furthermore, ethnic identification, group essentialism and protestant ethic were independently related to multiculturalism. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
118
2
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(143 citation statements)
references
References 46 publications
17
118
2
6
Order By: Relevance
“…The perception of essentialized migrant groups is thus threatening for majority groups, while it backs claims for recognition and social change among minority groups. A similar pattern of results was evidenced in a study on ingroup identification, showing that the more migrants identified with their group, the more they supported multiculturalism, while higher ingroup identification by majority members led to opposition to multiculturalism (Verkuyten & Brug, 2004;Verkuyten, 2005b). These findings suggest that ingroup identification by minority groups is associated with identity affirmation and the support of group-differentiated policies.…”
Section: Migration and Multiculturalism 18supporting
confidence: 78%
See 1 more Smart Citation
“…The perception of essentialized migrant groups is thus threatening for majority groups, while it backs claims for recognition and social change among minority groups. A similar pattern of results was evidenced in a study on ingroup identification, showing that the more migrants identified with their group, the more they supported multiculturalism, while higher ingroup identification by majority members led to opposition to multiculturalism (Verkuyten & Brug, 2004;Verkuyten, 2005b). These findings suggest that ingroup identification by minority groups is associated with identity affirmation and the support of group-differentiated policies.…”
Section: Migration and Multiculturalism 18supporting
confidence: 78%
“…Support for multiculturalism has also been examined as a function of perceived essentialism of migrant groups. Verkuyten and Brug (2004) showed that greater perceived essentialism of migrant groups reduced the support for multiculturalism among majority groups, while the opposite was true for minority groups: The more they perceived migrant groups as authentic and permanently different from majority groups, the more they supported multiculturalism. The perception of essentialized migrant groups is thus threatening for majority groups, while it backs claims for recognition and social change among minority groups.…”
Section: Migration and Multiculturalism 18mentioning
confidence: 99%
“…In contrast, majority group members generally prefer that the minority be assimilated (Zagefka et al, 2007). The more the majority group members identify with their in-group, the more they can be expected to try to protect their group interests and status (Verkuyten & Brug, 2004). Older, less educated people and extrinsic believers -characterized by an instrumental approach to religion -generally show less favourable attitudes towards cultural diversity.…”
Section: Analysing Multicultural Attitudes and Identitymentioning
confidence: 97%
“…In contrast, majority group members generally prefer that the minority be assimilated (Zagefka et al, 2007). The more the majority group members identify with their in-group, the more they can be expected to try to protect their group interests and status (Verkuyten and Brug, 2004). Older, less educated people and extrinsic believers -characterized by an instrumental approach to religion -generally show less favourable attitudes towards cultural diversity.…”
Section: Analysing Multicultural Attitudes and Identitymentioning
confidence: 97%